The Effectiveness Of Murottal Al-Qur'an Therapy And Virtual Reality To Reduce Pain Intensity In Post Operating Patients - Fadholi, Kirnawan; Mustofa, Akhmad (South East Asia Nursing Research, 2020)
Pain management in postoperative patients so far in the Shofa Room of PKU Muhammadiyah Hospital in Temanggung is still limited to pharmacotherapy in the form of 1 gram injection metamizole or 30mg ketorolac injection and the provision of deep breath therapy. Giving this therapy is not optimal in dealing with patient pain. Therefore other therapies need to be given for example non-pharmacology, one of them is a combination of murottal Al-Qur'an therapy and virtual reality when the pharmacotherapy reaction is finished and the complementary therapy has never been done in the room. The purpose of this study was to determine the effect of a combination of Murottal Al-Qur'an therapy and virtual reality on pain intensity in postoperative patients. The research design used in this study was quasi-experimental with a pre-posttest with a control group design approach. The subjects of this study were 32 post-operative patients at PKU Muhammadiyah Temanggung Hospital. The sampling technique used was purposive sampling. The instrument used in obtaining data is the Numeric Rating Scale. The results showed that: 1) there were differences in the average pretest and posttest intensity of postoperative pain in the intervention group with a p-value of 0,000; 2) there is a difference in the average pretest and posttest intensity of postoperative pain in the control group with a p-value of 0.003; and 3) there is a significant difference in the decrease in intensity of postoperative pain in the intervention group and the control group with a p-value of 0.009 where the experimental group showed a decrease in intensity more effectively than the control group. The results of this study indicate that the combination of Murottal Al-Qur'an therapy and virtual reality is effective in reducing pain intensity in postoperative patients.